The Effect of Work Stress, Communication, Work Ability on Employee Performance Through Job Satisfaction at PT. Global Way Indonesia in Pasuruan - Sahid Sumitro (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: Research aims to determine the Effect of Work Stress, Communication, Work Ability on Employee Performance through Job Satisfaction at PT. Global Way Indonesia Pasuruan. The population and samples in this study were employees at PT. Global Way Indonesia Pasuruan as many as 100 respondents. Design/methodology/approach: This research is a type of explanatory research, and the approach is Quantitative. The sampling method used in this study was saturated sampling. The instrument will be used using the Likert Scale. Data collection methods using primary data and secondary data and by using questionnaires, documentation and field research. Data processing techniques use validity test validity test, reliability test, description test, Data analysis technique using PLS. Version.3.0. Findings: The result of the study is that Work Stress does not have a direct effect on Job Satisfaction at PT. Global Way Indonesia Pasuruan. Communication directly affects Job Satisfaction at PT. Global Way Indonesia Pasuruan. Work Ability directly affects Job Satisfaction at PT. Global Way Indonesia Pasuruan. Work Stress directly affects Employee Performance at PT. Global Way Indonesia Pasuruan. Communication directly affects employee performance at PT. Global Way Indonesia Pasuruan. Work Ability directly affects employee performance at PT. Global Way Indonesia Pasuruan. Job Satisfaction directly affects Employee Performance at PT. Global Way Indonesia Pasuruan. Work Stress does not have an indirect effect on Employee Performance through Job Satisfaction at PT. Global Way Indonesia Pasuruan. Communication affects indirectly on Employee Performance through Job Satisfaction at PT. Global Way Indonesia Pasuruan. Work Ability affects indirectly employee performance through Job Satisfaction at PT. Global Way Indonesia Pasuruan. Practical implications: This research is expected to find research results that can contribute to the company PT. Global Way Indonesia Pasuruan. Originality/value: This is a Original paper Paper type: Research paper